The Effect of Burnout on Job Satisfaction Among Merchandising Employees in A Retail Company - Hikmatunnazilah; Sendi Satriadi; Dona Eka Putri; Siti Marliah Tambunan (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Merchandiser employees have duties and responsibilities in carrying out sales display marketing strategies on grocery shelves. Beyond the job satisfaction they experience, many merchandiser employees also experience burnout at work. The purpose of this study is to determine whether there is an effect of burnout on job satisfaction among employees in retail companies. The method used is a quantitative research method with 116 respondents. The data collection technique used in this study is purposive sampling, with questionnaire items distributed through Google Forms. The job satisfaction measurement tool used a scale consisting of 29 statement items compiled based on five dimensions, while the burnout measurement tool used a scale based on aspects of burnout consisting of 52 statement items. The results of this study indicate that the hypothesis is accepted, confirming the influence of burnout on job satisfaction among employees in retail companies. The correlation coefficient is r = 0.463, and the magnitude of the effect of burnout on job satisfaction is 0.214 (21.4%), with the remaining 0.786 (78.6%) influenced by other factors outside the research variables, such as marital status and employee self-achievement, with a significance value of 0.000 (p < 0.05). Based on the empirical mean calculation, the job satisfaction scores of the respondents in this study fall into the very high category, while the burnout scores fall into the medium category.